2020
DOI: 10.30880/ijie.2020.12.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Foundation Failures Mitigation under Expansive Clay by Using Granular Pile Anchor System

Abstract: Expansive soils are found in typical areas in the world especially in arid and semi-arid regions. The problems associated with this type of soil drive geotechnical engineers to invent new technologies as remediation’s such as physical and chemical treatments. Innovative foundation techniques were also suggested for remedying the swell-shrink problems of the expansive soil. The granular pile anchor (GPA) is relatively a more favorable technique indebted to its cost-effective, easy and fast to assemble and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Geotechnical engineers typically include cementitious additives [e.g., lime (Kasangaki and Towhata, 2009;Jung and Santagata, 2014) and fly ash (Puppala et al, 2001;Nalbantoğlu 2004;Hozatlıoğlu and Yilmaz, 2021)], noncementitious additives [e.g., stone dust (Reddy et al, 2015)], chemical additives [e.g., calcium chloride or magnesium hydroxide (Bhuvaneshwari et al, 2020) or sodium silicate (Reddy et al, 2015)], or gypsum (e.g., Yilmaz and Civelekoglu, 2009) as a stabilizing agent. Guar gum biopolymers (Acharya et al, 2017), commercially available polymers (Taher et al, 2020), wood/paper industry waste (Ijaz et al, 2020), hydrophobic polyurethane foam (Al-Atroush and Sebaey, 2021), along with physical methods such as granulated tire rubber (Patil et al, 2011) and pile anchoring systems (Sfoog et al, 2020) have also been suggested. Comprehensive experiments on expansion rates and treatment options for expansive soils are provided in Al-Rawas and Goosen (2006) and Zumrawi et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Geotechnical engineers typically include cementitious additives [e.g., lime (Kasangaki and Towhata, 2009;Jung and Santagata, 2014) and fly ash (Puppala et al, 2001;Nalbantoğlu 2004;Hozatlıoğlu and Yilmaz, 2021)], noncementitious additives [e.g., stone dust (Reddy et al, 2015)], chemical additives [e.g., calcium chloride or magnesium hydroxide (Bhuvaneshwari et al, 2020) or sodium silicate (Reddy et al, 2015)], or gypsum (e.g., Yilmaz and Civelekoglu, 2009) as a stabilizing agent. Guar gum biopolymers (Acharya et al, 2017), commercially available polymers (Taher et al, 2020), wood/paper industry waste (Ijaz et al, 2020), hydrophobic polyurethane foam (Al-Atroush and Sebaey, 2021), along with physical methods such as granulated tire rubber (Patil et al, 2011) and pile anchoring systems (Sfoog et al, 2020) have also been suggested. Comprehensive experiments on expansion rates and treatment options for expansive soils are provided in Al-Rawas and Goosen (2006) and Zumrawi et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Geotechnical engineers typically include cementitious additives [e.g., lime (Kasangaki and Towhata, 2009;Jung and Santagata, 2014) and fly ash (Puppala et al, 2001;Nalbantoğlu 2004;Hozatlıoğlu and Yilmaz, 2021)], noncementitious additives [e.g., stone dust (Reddy et al, 2015)], chemical additives [e.g., calcium chloride or magnesium hydroxide (Bhuvaneshwari et al, 2020) or sodium silicate (Reddy et al, 2015)], or gypsum (e.g., Yilmaz and Civelekoglu, 2009) as a stabilizing agent. Guar gum biopolymers (Acharya et al, 2017), commercially available polymers (Taher et al, 2020), wood/paper industry waste (Ijaz et al, 2020), hydrophobic polyurethane foam (Al-Atroush and Sebaey, 2021), along with physical methods such as granulated tire rubber (Patil et al, 2011) and pile anchoring systems (Sfoog et al, 2020) have also been suggested. Comprehensive experiments on expansion rates and treatment options for expansive soils are provided in Al-Rawas and Goosen (2006) and Zumrawi et al (2017).…”
Section: Introductionmentioning
confidence: 99%